Sustaining efforts to improve family well-being with parents with mental ill health and substance (mis)use - Allchin, Becca; Albermann, Kurt; Blake-Holmes, Kate; Gatsou, Lina; Hine, Rochelle; van Doesum, Karin; Nicholson, Joanne (Frontiers in Psychiatry, 2024)
Research conducted over the past 30 years has developed an extensive body of knowledge on families where parents experience mental ill health and/or substance (mis)use, and interventions that are effective in improving their outcomes. A more recent focus has also explored the importance and nuance of implementation. This perspective article reflects on the concept and practice of sustainability within this body of work and considers underlying assumptions in the field about the goal and direction of interventions that make clarity about sustainability difficult. We identify challenges for understanding sustainability, relating to how and who defines it, what is measured and the impact of context. We conclude by considering how we might be better able to plan and design for sustainability within this field.